The Impact of Ambient Air Pollution Toward Coronavirus Disease 2019 (Covid19): A Literature Review - Lulukatin Nasikhah; Aditya Sukma Pawitra (JURNAL KESEHATAN LINGKUNGAN, 2020)
Introduction: WHO has announced coronavirus Disease 2019 (Covid19) as a global pandemic at the immune decline, one of which is due to chronic exposure to ambient air pollution. This literature review aims to describe the impact of ambient air pollution toward the risk of being infected by Covid19. Discussion: Covid19 can be found in a bat (host primer), and can be contagious through a person, also possible from pets. The symptoms that sufferers will perceive are fever, cough, diarrhea, myalgia, fatigue, headache, nausea, vomit, abdominal pain, loss of appetite, and some asymptomatic people. The body's immunity affects a person's susceptibility to Covid19 infection. The body's immunity can be affected by ambient air pollution (with PM10, PM2,5, and O3 are the most pollutant in the air in various countries) for an extended period could be the reason for chronic illness (especially, respiratory tract) could reduce immune resistance. Furthermore, it might be happened on increasing at ACE2 activity and can cause increasing infected by Covid19. Prevention action can be done by contributing from all of the sectors at an observance in guarding, physical distancing, quarantine, and maintaining the ambient air quality in the future. Conclusion: Ambient air pollution must be considered as one effort to prevent chronic illness that can reduce immunity, which can increase the risk of being infected with Covid19. Furthermore, future studies will be carried out on ACE2 activity in people infected with Covid19 in order to get more valid results and following current conditions.